إسهامات المراجعة الداخلية في التقليل من المخاطر بالمؤسسات الاقتصادية - دراسة حالة مديرية توزيع الكهرباء والغاز، مؤسسة الدهن، مطاحن بلغيث الكبرى- ولاية سوق أهراس- - سها م عرعار; حنا ن شفرور (My University, 2022)
This study aimed to identify the role of internal audit in activating risk management in economic institutions, and for that a questionnaire study was conducted for a sample of institutions in the state of Souk Ahras and the study was prepared on the data collected through the questionnaire that was distributed to the selected sample. The study reached a set of results, the most important of which is that coordination is carried out within the internal audit department in order to improve risk management and through which the risks related to the institution are evaluated, and that the work of the internal auditor contributes significantly and in an advisory role to reducing risks, and that the internal audit activity helps to establish mechanisms effective control, and its activity includes monitoring and evaluating the effectiveness of the enterprise's risk management system. ........................................ هدفت هذه الدراسة إلى التعرف على دور المراجعة الداخلية في تفعيل إدارة المخاطر بالمؤسسات الاقتصادية، ومن أجل ذلك أجريت دراسة استبيانية لعينة من المؤسسات بولاية سوق أهراس وأعدت الدراسة على البيانات التي جمعت من خلال الاستبيان الذي تم توزيعه على العينة المختا رة. وقد توصلت الدراسة إلى مجموعة من النتائج أهمها أنه يتم التنسيق داخل قسم المراجعة الداخلية من أجل التقليل من المخاطر ومن خلالها يتم تقييم المخاطر المتعلقة بالمؤسسة، كما أن عمل المراجع الداخلي يسهم بشكل كبير وبدور استشاري في تقليل المخاطر، وأن نشاط المراجعة الداخلية يساعد على ترسيخ آليات فعالة للرقابة كما أن نشاطها يشمل مراقبة وتقييم فعالية نظام إدارة المخاطر في المؤسسة